Nationwide Analysis of the Distribution of Level 1 and Level 2 Trauma Centers Per Population Growth and Motor Vehicle Collision Injuries/Fatalities Utilizing Geographic Information Systems Mapping Technology: Toward Optimizing Access to Trauma Care. Issue 2 (10th February 2023) - Sen-Crowe, Brendon; Sutherland, Mason; McKenney, Mark; Elkbuli, Adel
Abstract : Background: Trauma centers (TCs) improve patient outcomes. Few investigations detail the US geographical distribution of Level 1 and 2 TCs (L1TCs, L2TCs) regarding motor vehicle collision (MVC) injuries/fatalities. Objective: We utilized Geographic Information Systems mapping to investigate the distribution of L1TCs and L2TCs in relation to population growth, MVC injuries, and MVC fatalities at the county and regional level to identify any disparities in access to trauma care. Methods: A cross-sectional analysis of L1TC and L2TC distribution, MVC injuries/fatalities, and population growth from 2010 to 2018. Information was gathered at the county and region level for young adults (aged 15–44), middle-aged adults (45–64), and elderly (≥65). Results: A total of 263 L1TCs across 46 states and 156 counties and 357 L2TCs across 44 states and 255 counties were identified. The mean distance between L1TCs and L2TCs is 28.3 miles and 31.1 miles, respectively. Seven counties were identified as being at-risk, all in the Western and Southern US regions that experienced ≥10% increase in population size, upward trends in MVC injuries, and upward trends MVC fatalities across all age groups. Conclusions: Seven US counties containing ≤2 ACSCOT-verified and/or state-designated L1TCs or L2TCs experienced a 10% increase in population, MVC injuries, and MVC fatalities across young, middle-aged and elderly adults from 2010 to 2018. This study highlights chronic disparities in access to trauma care for MVC patients. Evaluation of state limitations regarding the distribution of L1TCs and L2TCs, frequent evaluation of local and regional trauma care needs, and strategic interventions to improve access to trauma care may improve patient outcomes for heavily burdened counties.